Actuation of an electrohydraulic manipulator with a novel feedforward compensation scheme and PID feedback in servo-proportional valves. (June 2023) - Sarkar, Aniruddha; Maji, Krishnendu; Chaudhuri, Shouvik; Saha, Rana; Mookherjee, Saikat; Sanyal, Dipankar
Abstract: Achieving good tracking control beyond 0.1Hz by electrohydraulic manipulators still remains challenging due to the coupling of nonlinear actuation dynamics and multiple actuations. A novel order-separated feedforward, or FF, model has been proposed for estimating the major part of the commands of servo-proportional valves for metering their ports to monitor oil flow in the paired cylinders. Motion studies have been executed in serial manipulation mode by using such control to two valves and in serial–parallel mode to eight valves. Oil leakage and cylinder friction have been included as lower-order effects for the narrow radial clearance and near-zero lap in the valves each paired with a low-friction cylinder. Other assumptions of negligible inertia and suspended weight under the pistons have been validated by a numerical exercise. A PID feedback has been added during real-time tracking by an FFPID controller. Reciprocating and circular motion demands in the serial mode and heave tracking in serial–parallel mode, all in a vertical plane, have been executed. More precise and smoother tracking has been achieved up to 1Hz in the serial mode mostly with lower expense of energy than a conventional PID-alone controller. Results indicate FF guidance to mitigate oscillations occasionally apparent in PID-only case due to either hunting among multiple solutions or gain sensitivity of the nonlinear system. Good heave tracking has been obtained up to 0.2Hz. Substantial disturbance rejection capability of the controller has been demonstrated against tension arising from the connecting oil hoses. A potential use of the FF model in diagnosing emerging valve or cylinder fault with their aging has also been explained. Highlights: Real-time feedforward-PID control for electrohydraulic mini-manipulator system. Order-separated feedforward for multiple nonlinearities in any double-acting cylinder. Stability analysis shows D gain as necessary for low-inertia mini-manipulator system. Estimation of feedforward parameters and PID gains by GA-based identification. Precise tracking faster than existing manipulators despite significant disturbance. Graphical abstract: